STRUKTUR DAN FUNGSI MITOS MBAH NGANTEN DI DESA TANGGUNGKRAMAT - Indah Puspitasari (STKIP PGRI Jombang, 2022)
AbstractThis study aims to determine the structure and function of myths in Kramat hamlet, Tanggungkramat village, Ploso sub-district, Jombang district. The method used in this research is interview technique and data transcription. In this study, it was found that the myth in Kramat hamlet is still highly trusted by the surrounding community and influences the daily life of the people of Kramat hamlet, Tanggungkramat village, Ploso District, Jombang Regency. After conducting research, collecting data, then analyzing it, the structure and functions contained in the myths in Kramat hamlet, Tanggungkramat village are obtained as follows. (1) geographical level, covering the character's journey until the myth occurs; (2) the economic level, including the community's desire for a job, the work of one of the figures to be imitated by the community, and the work of the community related to the figure; (3) the sociological level, including the relationship between the figures and the community; (4) the cosmological level, which includes things that rarely actually happen in the world. The functions contained in the myths in the village of Tanggungkramat include (1) as a form of entertainment, the community holds village alms for certain purposes; (2) As a means of legalizing cultural institutions and institutions, the community asks for the help of the three mythical figures so that what is planned goes smoothly; (3) as a means of educating children, instilling a trusting and helpful attitude; (4) as a coercive and supervisory tool so that community norms will always be obeyed by collective members, there are rules or prohibitions that must be obeyed or implemented by the community.Keywords: Myth, Structure, Function.